Perceived Stress at Work and Associated Factors among E-Waste Workers in French-Speaking West Africa - Kêdoté, Nonvignon Marius; Sopoh, Ghislain Emmanuel; Tobada, Steve Biko (My University, 2022)
Perceived stress at work is an important risk factor that affects the mental and physical health of workers. This study aims to determine the prevalence and factors associated with perceived stress in the informal electronic and electrical equipment waste processing sector in French-speaking West Africa. From 14 to 21 November 2019, a cross-sectional survey was carried out among e-waste workers in five countries in the French-speaking West African region, and participants were selected by stratified random sampling. Participants were interviewed on socio-demographic variables and characteristics related to e-waste management activities using a questionnaire incorporating Cohen’s Perceived Stress Scale (10-item version). Factors associated with perceived stress were determined by multivariate logistic regression. A total of 740 e-waste workers were interviewed. The mean age of the workers was 34.59 11.65 years, with extremes of 14 and 74 years. Most of the interviewees were repairers (43.11%). The prevalence of perceived stress among the e-waste workers was 76.76%. Insufficient income, number of working days per week, perceived violence at work, and the interference of work with family responsibilities or leisure were the risk factors that were the most associated with perceived stress. The high prevalence of perceived stress and its associated factors call for consideration and improvement of the working conditions of e-waste workers.
Keywords: perceived stress; work; associated factors; e-waste; West Africa